Dr. Reem Al-Terkawi — Deep Plane Facelift - Al-Terkawi, Reem (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Reem Al-Terkawi. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002952; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS